Formulating An Effective Marketing Strategy For Warung Nasi Ambu Rini Through The Optimization of Stp And Marketing Mix (7p) - Agus Muhamad Kemal Fauzan, Mas (Publisher Cv. Inara, 2026)
This paper investigates marketing issues of Warung Nasi & Sate Ambu Rini which is a traditional Sundanese Restaurant in Bandung and comes up with a well-rounded marketing strategy that will help fill in the gaps. Although the quality of products and customer satisfaction with current customers are high, the warung cannot convert this to the wider awareness of the product and customer attraction. It has used a single case study where the research is conducted qualitatively using thematic analysis. In-depth interviews with 16 respondents of four categories of stakeholders (owner, employees, current customers, and potential customers) and six hours of non-participant observation were used to gather primary data. Secondary data comprised menu documentation, Instagram and Tik Tok social media analytics, GoFood data of the merchant dashboard, and photographs of the physical environment. The main results indicate that there is a critical gap in awareness (walk-in customers are zero and the social media reach decreases to -64.1% after 90 days), positioning communication (professional branding creates higher price expectations (Rp 35,000-45,000) than actual prices (since the minimum price is Rp 15,000)), delivery channel (nothing is commissioned through GoFood), targeting (students and young professionals are underrepresented), and promotion (the Instagram engagement rate is 0.32 The research suggests the positioning of the company in a Premium Feel, Everyday Price and the recommendations given are reflecting GoFood menu optimization, regular social media postings with price-inclusive information, systematic referral plans and exterior signage change. A measurement framework somewhat based on SMART would provide accountability in implementation.